Review of the Physical Condition of Bukittinggi City Wrestling Athletes - Purnomo, Angga; Irawadi, Hendri; Putra, Yogi Arnaldo; Putra, Juanda (Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2024)
Studi Purpose This study aims to determine the level of physical condition of male wrestling athletes in the city of Bukittinggi. Method This research uses a type of descriptive research which consists of analyzing descriptions of symptoms or situations of certain objects. The population of this study was all wrestling athletes in the city of Bukittinggi, totaling 10 athletes with a sample size of 10 athletes determined using total sampling techniques. Results of data analysis of the frequency distribution of the physical condition of male wrestling athletes in the city of Bukittinggi, namely: 1) the level of arm muscle strength of male wrestling athletes in the city of Bukittinggi using pull ups is in the good category with an average value of 11. 2) the level of reaction speed of male wrestling athletes in the city Bukittinggi using the Whole Body Reaction tool is included in the medium category with an average value of 0.802. 3) the level of flexibility of male wrestling athletes from the city of Bukittinggi using Bridge-Up is included in the medium category with an average score of 40.75. 4) the level of aerobic endurance of male wrestling athletes in the city of Bukittinggi bleep test is included in the good category with an average score of 43.24.